Pengaruh Model Pembelajaran TPS (Think Pair Share) Terhadap Kemampuan Literasi Lingkungan Siswa Kelas X MAN 1 Samarinda: Pengaruh Model Pembelajaran TPS (Think Pair Share) Terhadap Kemampuan Literasi Lingkungan Siswa Kelas X - Sayyidaturrofi'ah, Wafi; Nasution, Ruqoyyah; Masitah, Masitah; Purwati, Sri (PendIPA Journal of Science Education, 2025)
This study aimed to determine the effect of the Think Pair Share (TPS) learning model on students’ environmental literacy skills in Grade X at MAN 1 Samarinda. The research employed a quantitative approach using a quasi-experimental method with a Pretest-Posttest Control Group Design. The sample consisted of class XF and XG, each comprising 30 students. Sampling was conducted using the Simple Random Sampling technique, resulting in class XF as the experimental group and class XG as the control group. To measure students’ environmental literacy covering knowledge, cognitive skills, attitudes, and environmental behavior the N-Gain test was applied. The results of the N-Gain analysis showed that the control group experienced an increase in the low to moderate category, while the experimental group demonstrated more significant improvement, particularly in the behavioral domain, which obtained an N-Gain score of 0.86 categorized as high. This indicates the effectiveness of the TPS model in encouraging changes in students’ environmental behavior. Furthermore, hypothesis testing was conducted using the Mann-Whitney U test with a 5% significance level. The results showed a p-value of 0.001 < 0.05, indicating that H0 was rejected and H1 was accepted, meaning there was a statistically significant difference. Thus, it can be concluded that the Think Pair Share learning model has a significant effect on students’ environmental literacy in Grade X at MAN 1 Samarinda.